2021
DOI: 10.1266/ggs.20-00057
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of differentially expressed genes as prognostic markers in pheochromocytoma and paraganglioma tumors

Abstract: The pathogenesis of pheochromocytoma and paraganglioma (PCPG) catecholamine-producing tumors is exceedingly complicated. Here, we sought to identify important genes affecting the prognosis and survival rate of patients suffering from PCPG. We analyzed 95 samples obtained from two microarray data series, GSE19422 and GSE60459, from the Gene Expression Omnibus (GEO) repository. First, differentially expressed genes (DEGs) were identified by comparing 87 PCPG tumor samples and eight normal adrenal tissue samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…23 WNT2B was upregulated in ischemic brain damage and was related to the repair process of brain damage. 19 These studies hinted that WNT2B might be associated with the pathogenesis of IS. Previously, genetic variants in WNT2B were associated with various diseases, such as melanoma, 24 microphthalmia, anophthalmia, coloboma, 25 and bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 WNT2B was upregulated in ischemic brain damage and was related to the repair process of brain damage. 19 These studies hinted that WNT2B might be associated with the pathogenesis of IS. Previously, genetic variants in WNT2B were associated with various diseases, such as melanoma, 24 microphthalmia, anophthalmia, coloboma, 25 and bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previously, the Wnt signaling pathway-related WNT2B gene was upregulated in ischemic brain damage. 19 A multiancestry genome-wide association study displayed that WNT2B rs12037987 was associated with stroke. 20 Masoumeh Pourasgari et al reported WNT2B rs12037987 was an effective stroke locus for stroke risk with function information.…”
Section: Introductionmentioning
confidence: 99%
“…AKR1B1 is involved in a complex network of signaling pathways, including oxidative stress, inflammation, and epithelial–mesenchymal transition [ 7 ]. Downregulating AKR1B1 reportedly leads to poor prognosis and significantly impacts survival in patients with pheochromocytoma and paraganglioma tumors [ 8 ]. AKR1B1 downregulation is also reported in hepatocellular carcinoma [ 9 ], endometrial cancer [ 10 ], sporadic adrenocortical tumors [ 11 ], and prostate cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%